Villages and Urbanization. Issue 1 (2nd January 2017) - Stringer, Ben
Abstract: In this article comments by politician Boris Johnson and economist Edward Glaeser exemplify narratives of global urbanization that portray rural villages as redundant and perpetuate outdated notions of urban–rural division. Simultaneously, traditional urban–rural dialectics are distorted by divisive new urban projects like gated communities styled as villages. This paper argues for development models that acknowledge the vital environmental and economic roles played by rural villages, and opposes artificially created "villages" in cities. In so doing, alternative readings of rurality and villages by Rem Koolhaas, Brazilian land reformers, Mahatma Gandhi, and critics of contemporary Indian literature and urbanism are considered.